ENHANCING EDUCATIONAL REPUTATION THROUGH MUTUAL PUBLIC RELATIONS: A PSYCHOLOGICAL PERSPECTIVE - Darina, Arini Nuora; Husna, Fatimatul; Holifah, Holifah; Sukriyah, Toyyibatul Mukminatus; Yaqin, Moh Ainol (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to explore ways to improve the reputation of education through mutual community relations, with a psychological approach as an analytical framework. The method used in this research is a qualitative study, which involves in-depth interviews with educational institution managers and community members, as well as content analysis of various community relations programs that have been implemented. The research results show that open and transparent communication, active involvement in social activities, and a deep understanding of community needs and aspirations can significantly improve the reputation of educational institutions. Additionally, this research found that psychological approaches, such as building trust and empathy, play an essential role in creating mutually beneficial relationships between academic institutions and society. The implications of this research emphasize the need to develop community relations strategies that are more integrated and responsive to social dynamics to strengthen educational institutions' positive image in the public's eyes.